Gaya Kepemimpinan, Kohesivitas Kelompok, dan Komitmen pada Partai Politik - Budiharto, Yos; Koentjoro, Koentjoro (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
Organizational commitment has been conceptualised and measured in various ways. The current study was conducted to test aspects of three component model of organizational commitment which integrates the various concepts.  The three component of organizational commitment in this study are affective, continuance and normative commitment. The proposed independent variables were transformational leadership, transactional leadership and group cohesiveness which were assumed to have significant relationship with organizational commitment. The data of this study were collected through questionnaires carried out to 120 cadres who were active in one political party, considered as nationalist– secular party, in Yogyakarta. The study revealed that the three independent variables are empirically undifferentiated to the three components model of organizational commitment. Specifically, this study found that transformational leadership, transactional leadership, group cohesiveness, age and length of cadre membership are positively and significantly related to continuance commitment. When tested individually, it shows that age did not have positive relationship with the three component model of commitment.     Key Words: Leadership Styles,  Group Cohesiveness,  Commitment